IMPLEMENTATION OF MIND MAPPING LEARNING MODEL TO IMPROVE LEARNING OUTCOMES OF CIVIL EDUCATION SUBJECT - Fauzi, Zain Ahmad; Degeng, I Nyoman Sudjana (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2018)
This research is to describe the implementation of mind mapping learning model that can improve the learning outcomes of civil education subject. This research was conducted at Public Elementary School Mawar 2 of Banjarmasin, specifically on grade 5 students involving 29 students consisting of 13 male students and 16 female students. This research is classroom action research. The data analysis used was descriptive quantitative. The research results show the learning outcome of students on Civil Education subject is improving in every meeting. Therefore, mind mapping learning model can improve learning outcome of students.